STUDIES ON RADIATION PASTEURISATION OF MEDIUM FATTY FISH II. PRECURSORS OF YELLOW DISCOLOURATION IN IRRADIATED WHITE POMFRET (STROMATEUS CINEREUS) - KUMTA, U S; KAMAT, S V (Fishery Technology, 2025)
Triglycerides, phospholipids and sarcoplasmic proteins fractions of white pomfret produced considerable amounts of thiobarbituric acid reactive substances (TBRS) on irradiation. Incubation of malonaldehyde with pomfret skin under aseptic conditions developed yellow pigmentation of the skin tissues, similar in spectral characteristics to those produced on irradiation of the skin.